Analisis Kinerja Keuangan Serta Pengaruhnya Terhadap Return Saham Pada Perusahaan Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021 (Studi Empiris Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Farah Wirdatul Baidla; Ronny Malavia Mardani; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to examine the effect of Economic Value Added, Market Value Added, Refined Economic Value Added and Financial Value Added on Stock Returns. This research is classified as Explanatory Research using quantitative methods. The population in this study are all companies in the food and beverage sector on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used is a saturated sample because the number of samples is limited to 22 companies. The data used in this research is secondary data accessed through the official website of the Indonesia Stock Exchange. Data analysis using SPSS 29.0 analysis. with the aim of examining the effect of Economic Value Added (X1), Market Value Added (X2), Refined Economic Value Added (X3) and Financial Value Added (X4) on Stock Returns (Y). This study has the results of Market Value Added have a negative and not significant to Stock Return, Financial Value Added and Refined Economic Value Added are positive but not significant to Stock Returns.. Meanwhile, Economic Value Added shows a positive and significant value on stock returns. Keywords : Economic Value Added, Market Value Added, Refined Economic Value Added, Financial Value Added, Stock Return.